2008
DOI: 10.31899/rh4.1212
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing utilization of the findings from the youth reproductive health project in Senegal

Abstract: In 1999, FRONTIERS began a three-year collaboration with the World Health Organization (WHO), the Senegalese ministries of Education (MOE), of Youth (MOY), and Family and Social Affairs (MOFSA), the Center for Research and Training (CEFOREP) and the Population Training Group (GEEP) to test the feasibility, effectiveness and cost of school-, clinic-, and community-based interventions to improve the reproductive health of youth aged 10-19 years. The Operations Research (OR) study focused on providing information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Enrolling all household members in the NHIS is also not expected to exert a heavy burden on the majority of households as they would be expected to spend 5.9% of their non-food expenditures or only 2.0% of total expenditure on health insurance. This is close to the 5.0% and 1.2% reported by Diop [ 32 ] in the study in Senegal. A recent study [ 51 ] in Ghana suggests that about 30% of the 65% of the NHIS members who are exempted from paying premiums could indeed afford to contribute.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Enrolling all household members in the NHIS is also not expected to exert a heavy burden on the majority of households as they would be expected to spend 5.9% of their non-food expenditures or only 2.0% of total expenditure on health insurance. This is close to the 5.0% and 1.2% reported by Diop [ 32 ] in the study in Senegal. A recent study [ 51 ] in Ghana suggests that about 30% of the 65% of the NHIS members who are exempted from paying premiums could indeed afford to contribute.…”
Section: Discussionsupporting
confidence: 90%
“…What constitutes affordable premium however lacks a clear economic definition, though attempts have been made to estimate it in the developed world [ 27 - 29 ]. In the few studies in Africa which have looked at the premium as a barrier to enrolment or retention in health insurance schemes, attempts have not been made to estimate what constitutes affordable insurance contributions [ 13 , 14 , 30 , 31 ], though few have analysed household capacity to pay the insurance premium [ 32 , 33 ]. These studies have reported mixed results on whether affordability is the main barrier to enrolment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this aim of containing adverse selection in the NHIS has not been fully achieved because although by design the NHIS is mandatory for all people living in Ghana, in practice it is voluntary because there is no legal enforcement, making it possible for low risk individuals to opt out living high risk individuals mostly from the exemption groups in the insurance pool. Other studies from community-based health insurance schemes in Africa by Atim [ 39 ] and Diop [ 40 ] also pointed to similar conclusions.…”
Section: Discussionsupporting
confidence: 64%
“…Differences in religious and cultural norms may account for the differences in knowledge about sexuality topics from country to country. For example in Dakar, Senegal, religious leaders believed that parents should discuss reproductive health issues openly with their children, but parents lack the knowledge to do so with confidence [ 26 ]. On the contrary, talking about sex and sexual activities with adolescents in Ghana is perceived as a cultural taboo.…”
Section: Discussionmentioning
confidence: 99%